2007
DOI: 10.1002/app.26842
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and steric effects of methyl substituent in Samarium (III) phenolates on their initiation activities in polymerization of ϵ‐caprolactone

Abstract: Seven phenols with methyls substituting ortho or para hydrogens are firstly reported as ligands for Samarium (III) complexes. The resultant Samarium (III) phenolates were used as single component initiators for ring-opening polymerization (ROP) of e-caprolactone (CL). The results were in good order and met well with structural changes in phenol ligands. To explain the ordered correlation between ROP results and ligand structures of these phenolates, quantum chemical (QC) method was applied to optimize the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In complex 3 , the La(1)‐O(3) and La(1)‐O(5) coordination bond lengths (2.475 Å and 2.468 Å) are similar to the values for [La(O 2 CC 6 H 2 Me 3 –2,4,6) 2 (μ‐O 2 ‐CC 6 H 2 Me 3 –2,4,6)(DMSO) 2 ] 2 (2.459 Å) . The La(1)‐N(2) and La(1)‐N(3) coordination bond lengths (2.523 Å and 2.547 Å) are longer than that of [Li(DME) 3 ][MeCpLa(NPh 2 ) 3 ] (2.443 Å), but shorter than that of La(Me 2 NC 2 H 4 CP) 3 (2.898 Å) …”
Section: Resultssupporting
confidence: 70%
“…In complex 3 , the La(1)‐O(3) and La(1)‐O(5) coordination bond lengths (2.475 Å and 2.468 Å) are similar to the values for [La(O 2 CC 6 H 2 Me 3 –2,4,6) 2 (μ‐O 2 ‐CC 6 H 2 Me 3 –2,4,6)(DMSO) 2 ] 2 (2.459 Å) . The La(1)‐N(2) and La(1)‐N(3) coordination bond lengths (2.523 Å and 2.547 Å) are longer than that of [Li(DME) 3 ][MeCpLa(NPh 2 ) 3 ] (2.443 Å), but shorter than that of La(Me 2 NC 2 H 4 CP) 3 (2.898 Å) …”
Section: Resultssupporting
confidence: 70%
“…One possibility is via insertion of the monomer into the metal-phenoxide bond, as has been proposed for Sm tris(phenolate) species. 28 In previous studies of ROP using amine-bis(phenolate) Ln species, the Ln-phenolate bonds were considered inert and the monomer only inserted into the metal amide or alkyl bond in these related lanthanide-amide andalkyl lactone ROP initiators. 15, 18 However, in our study no ligand related end groups that would suggest this insertion mechanism were observed in the 1 H NMR spectra of the polymer products.…”
Section: Reactivity Of Ln-cl Complexes Towards E-caprolactonementioning
confidence: 99%
“…27 Samarium tris(phenolate) complexes have recently been reported as initiators for e-CL ROP and their mechanism studied in some detail. 28 It was proposed that e-CL insertion occurs at all three Sm-O bonds and although in Scheme 2 insertion is only shown into one Ln-O bond, it may well be occuring at both reactive bond sites. After repeated coordination and migratory-insertion steps, termination is likely occuring via nucleophilic attack of the 'phenol' oxygen at the Ln metal centre and subsequent 'back-biting' of the growing polymer chain to yield cyclic polyesters of narrow polydispersity.…”
Section: Reactivity Of Ln-cl Complexes Towards E-caprolactonementioning
confidence: 99%
“…2,6-Di-tertbutyl-4-methylphenol and the lanthanide showed relative higher chemoselectivity, which might have resulted from substituent's electronic/steric effect and metal characteristic. 29,30 To demonstrate the versatility of rare earth catalysts, polymerization reactions with different monomer feed ratios were carried out to obtain varied molecular weights of PCLSH using 8 as the catalyst. On increasing [CL]/[MH] from 40 to 200, a wide range of molecular weights from 6870 to 20 450 g mol À1 were achieved within 2 h, which were in good accordance with the M n,theo values.…”
Section: Resultsmentioning
confidence: 99%